2023
DOI: 10.3390/agriculture13081493
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Analysis Revealed the Role of Silicon in Modulating Salinity Stress in Mung Bean

Abstract: Salinity stress acts as a significant deterrent in the course of optimal plant growth and productivity, and mung bean, being a relay crop in the cereal cropping system, is severely affected by salinity. Silicon (Si), on the other hand, has exhibited promising outcomes with regards to alleviating salinity stress. In order to understand the critical mechanisms underlying mung bean (Vigna radiata L.) tolerance towards salt stress, this study examined the effects of different salinity concentrations on antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Mung bean tolerance to salinity is related to physiological processes in the plant. Previous studies revealed that the level of tolerance of mung bean to salinity is related to membrane permeability and cell osmotic pressure (Nawaz et al 2021;Al Murad et al 2023), its ability to accumulate K (Hao et al 2021;Joshi et al 2022), its ability to inhibit Na translocation from root to shoot (Hu et al 2022), its ability to accumulate water in leaves, proline and glycine betaine, and inhibit chlorophyll degradation (Shafi et al 2019;Sofy et al 2020;). Tolerance in mung beans is also related to enzymatic reactions in the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mung bean tolerance to salinity is related to physiological processes in the plant. Previous studies revealed that the level of tolerance of mung bean to salinity is related to membrane permeability and cell osmotic pressure (Nawaz et al 2021;Al Murad et al 2023), its ability to accumulate K (Hao et al 2021;Joshi et al 2022), its ability to inhibit Na translocation from root to shoot (Hu et al 2022), its ability to accumulate water in leaves, proline and glycine betaine, and inhibit chlorophyll degradation (Shafi et al 2019;Sofy et al 2020;). Tolerance in mung beans is also related to enzymatic reactions in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Tolerance in mung beans is also related to enzymatic reactions in the cell. Increasing salt concentration from 50 to 200 mM NaCl increased catalase activity 2.4 times and peroxidase 2.8 times (antioxidative enzymes) (Al Murad et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…TFC was determined spectrometrically, according to Atanassova et al [26], and was expressed as mg of catechin equivalents (CE) g −1 . Soluble carbohydrates were evaluated using the anthrone method, according to Al Murad and Muneer [27]. The supernatant (50 µL) from the methanolic extract was transferred to the solution with 950 µL of distilled water, and 2.5 mL of 0.2% anthrone reagent was added.…”
Section: Leaf Biochemical Analysis (Chlorophyll and Carotenoid Conten...mentioning
confidence: 99%
“…With the increasing degradation of arable land and the escalating frequency of extreme weather events, it has become imperative to comprehend and mitigate the adverse effects of salt stress on crops [9]. In recent years, diverse strategies have been explored to mitigate the deleterious impact of salt stress on plants, including plant growth regulators [10,11], plant hormones [12][13][14], nanoparticles [15][16][17], nutrient elements [18,19], and aqueous extracts [20].…”
Section: Introductionmentioning
confidence: 99%